2020
DOI: 10.1111/jgh.15180
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant transarterial chemoembolization to sorafenib in unresectable hepatocellular carcinoma: A meta‐analysis

Abstract: Background and Aim An increasing number of transarterial chemoembolization (TACE) plus sorafenib combination therapy has been applied for unresectable hepatocellular carcinoma (HCC). However, it remains controversial whether combination therapy is superior to sorafenib monotherapy. Therefore, we aimed to perform a meta‐analysis to evaluate the efficacy and safety of the combination therapy of TACE plus sorafenib for unresectable HCC. Methods This meta‐analysis was based on the relative outcomes from a specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…Therefore, many studies have adopted TACE combined with systemic therapy for the treatment of unresectable HCC ( 27 ). TACE combined with sorafenib and lenvatinib, respectively, are commonly used in unresectable HCC ( 6 , 28 30 ). The possible mechanism is that TACE induces angiogenesis and enhances the serum concentrations of VEGF because of local hypoxia, suggesting that VEGF may exert its greatest antiangiogenic effects before or after TACE ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, many studies have adopted TACE combined with systemic therapy for the treatment of unresectable HCC ( 27 ). TACE combined with sorafenib and lenvatinib, respectively, are commonly used in unresectable HCC ( 6 , 28 30 ). The possible mechanism is that TACE induces angiogenesis and enhances the serum concentrations of VEGF because of local hypoxia, suggesting that VEGF may exert its greatest antiangiogenic effects before or after TACE ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…These adverse events may lead to reduction and suspension of sorafenib therapy, which should be considered in clinical practice. However, in a meta-analysis by Chen et al, 55 the authors found no significant differences in adverse events between combination therapy and sorafenib monotherapy. In addition, some clinical trials have indicated that the safety and tolerance of TACE plus sorafenib are acceptable.…”
Section: Discussionmentioning
confidence: 93%
“…They thought that OS and time to progression (TTP) of combined treatment were significantly better than monotherapy. Chen et al (66) believed that compared to the monotherapy group, the combined treatment group showed a significant increase in OS, TTP, and ORR. Also, there was no statistically significant difference in the incidence of AEs between the two treatment groups.…”
Section: Discussionmentioning
confidence: 99%